2009
DOI: 10.1519/jsc.0b013e3181b8d5c1
|View full text |Cite
|
Sign up to set email alerts
|

Percentile Values for Muscular Strength Field Tests in Children Aged 6 to 17 Years: Influence of Weight Status

Abstract: The aim of this study was to provide percentile values for 9 different muscular strength tests for Spanish children (1,513 boys and 1,265 girls) aged 6 to 17.9 years. The influence of body weight on the muscular strength level across age groups was also examined. Explosive strength was assessed by the throw ball test (upper body), standing broad jump, and vertical jump tests (lower body). Upper-body muscular endurance was assessed by push ups, bent arm hang, and pull ups tests, and abdominal muscular endurance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
120
0
25

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(173 citation statements)
references
References 44 publications
28
120
0
25
Order By: Relevance
“…All these studies, in particular, have observed increased performance values for strength (e.g., Hand-grip), power (e.g., standing broad jump), agility (e.g., 4 × 10-m shuttle run), muscular endurance (e.g., Sit-ups), and endurance (e.g., 20 m shuttle run test) [27,28]. The reported tests are all included in our ASSO FTB, except for the endurance measures.…”
Section: Discussionmentioning
confidence: 99%
“…All these studies, in particular, have observed increased performance values for strength (e.g., Hand-grip), power (e.g., standing broad jump), agility (e.g., 4 × 10-m shuttle run), muscular endurance (e.g., Sit-ups), and endurance (e.g., 20 m shuttle run test) [27,28]. The reported tests are all included in our ASSO FTB, except for the endurance measures.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, P 50 of 20mSRT was 48.1 ml kg − 1 min − 1 vs 47.3 ml kg − 1 min − 1 for Spanish and European boys, respectively, and 46.7 ml kg − 1 min − 1 vs 46.2 ml kg − 1 min − 1 for Spanish and European girls, respectively. Castro-Pinero et al 44 published percentile values for muscular strength (standing long jump) 43 and CRF (20mSRT, stages) in children and adolescents from Cadiz (Spain) aged 6-17 years. Our results are also comparable to those from Castro-Pinero et al 43,44 for those children aged 6-9 years.…”
Section: S63mentioning
confidence: 99%
“…Castro-Pinero et al 44 published percentile values for muscular strength (standing long jump) 43 and CRF (20mSRT, stages) in children and adolescents from Cadiz (Spain) aged 6-17 years. Our results are also comparable to those from Castro-Pinero et al 43,44 for those children aged 6-9 years. For example, P 50 of standing long jump was 111.6 cm vs 120.5 cm for Spanish and European boys, respectively, and 114.8 cm vs 110.7 cm for Spanish and European girls, respectively.…”
Section: S63mentioning
confidence: 99%
“…According to this definition, isometric contractions or high intensity low volume contractions can be considered accurate and reliable methods to assess strength. According to our search criteria, the systematic review highlighted a mainly adopted test for the assessment of upper body maximal strength: the HG, with a number of 10 retrieved records [66,124,[139][140][141][142][143][144][145][146] (Table 3). Other tests found through the bibliographic search were: the 30 s push-up test, the arm-hang test and the handheld myometer tests (this last test is equivalent to the hand grip strength predictiveness test), the push-up to failure test, the pull-up test and the overhead medicine ball throw [117,127,128 2014 cross-sectional n.a.…”
Section: Strengthmentioning
confidence: 99%